Gustav Vasa 500 år ; 1496 - 1996 ; stora jubileumsboken = The official anniversary book of the great Swedish King Gustav Vasa - Åberg, Alf 1916-2011 (Norstedts ; Hembygdsförlag, 1996)
Produced for the 500th anniversary of the birth of Gustav Vasa, this book is intended as an introduction and an elementary survey of the events of the life and times of the king in 16th century Sweden.
Keywords: Gustav <I Vasa, King of Sweden, 1496-1560>; Biografie; Festschrift